Development of a fluorescent three‐hybrid system for the identification of protein‐protein associators. Issue 1 (5th June 2020) - Foster, Andrew D.; Chung, Chun‐wa; Hann, Michael M.; Simpson, Graham L.; Tavassoli, Ali
Abstract: The chemically‐induced dimerization of proteins is fundamental to many key regulatory pathways. A number of natural products exert their downstream effect through the stabilization of a protein complex, either by direct binding to two distinct protein partners or via an allosteric mechanism. Here, we report a bacterial three‐hybrid system, with dual life/death and fluorescent reporters, which detects protein association and is compatible with high‐throughput screening. We use rapamycin mediated mTOR‐FKBP12 (mammalian target of rapamycin—FK506 Binding Protein 12 kDa) dimerization to validate this platform; the addition of rapamycin results in the association of these target proteins, leading to the expression of two essential life/death reporter genes and a fluorescent signal. We further used this system to quantify the activity of rapamycin by utilizing the fluorescent readout, exemplifying its potential in screening and for ranking large in vivo libraries for compounds that upregulate the association of any two given proteins. Abstract :